The Relationship between Teachers’ Self-Disclosure and EFL Students’ Motivation for Class Participation - KUHZAD, Sara; ZARFSAZ, Elham (LPPM Universitas Advent Indonesia, 2023)
A communication technique specifically used to improve relationships between teachers and students is teacher self-disclosure. More often than not, a healthy learning environment is created by the relationship between the teacher and students (Frymier & Houser, 2000). The purpose of this study was to determine whether there are any variations between male and female students' motivation regarding the teachers' self-disclosure and to investigate the relationship between teachers' self-disclosure and EFL students' motivation for class participation. In order to accomplish these goals, 28 teachers and 108 intermediate English learners from three institutions—Andishe Sabz Ehsan institution, Arad institution, and Maqreb Zamin institution—who were both male and female students were chosen to take part in the study. Data was then gathered using the teachers' self-disclosure questionnaire and the students' motivation questionnaire. The study's findings suggested a strong correlation between teachers' self-disclosure and EFL students' motivation to participate in class, however, there was no difference in motivation between male and female students with regard to teachers' self-disclosure. The findings of this study suggest that TSD can be used as a teaching and career development tool by EFL instructors at schools, universities, and other English language institutions to enhance learning and motivate students to learn English in the most effective manner.